Socio-Economic Change Brought by Forced Mass Migrations in 1947: The Impact of Forced Mass Migrations in the Partition of the Punjab (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The partition of the Punjab enforced movements of the people on a scale absolutely unparalleled, in the history of the world. It is probably true that there has never been such a huge exchange of population. In the East Punjab and the West Punjab, the minorities were made to quit their homes in the most adverse circumstances, created by communal riots and they had to reach the country of their destination very often as paupers. The massive exchange of population that attended the partition of the Punjab and the conditions under which it took place are almost unprecedented in history. This task was successfully accomplished by the East Punjab Government with mature guidance and financial support of the central government.